Cloning of an antiporter gene (NHX1) from PCR amplicons into a recombination competent vector containing a constitutive promoter (caMV35S) - Razzaque, Samsad (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2011